Misalignment - the core challenge in integrating security and privacy requirements into mobile banking application development - Machiridza, Memory (Department of Information Systems, 2016)
This study identifies and explores the core challenge faced when integrating security and privacy requirements into the mobile banking software development life cycle. Studies on key issues in Information Systems (IS) have been on-going for several decades, with security and privacy moving up the ranks of top issues in IS. Security and privacy requirements can be added into the mobile application development processes by practising secure coding, and/or, by adding a third party security tool. This study gathered data from a single case study; it employs grounded theory methodology to reveal misalignment as the core challenge to integrating security and privacy requirements into mobile banking application development. The forms of misalignment are between security and privacy requirements and (1) external entities, (2) roles, (3) skills and (4) system requirements. The nature of the mobile application domain results in the misalignment forms identified above. Some of the findings indicate the need for further research. Research indicates that mobile application development follows agile methods for development. Agile methods have been compared with Complex Adaptive Systems (CAS). For this reason, research in IS could benefit from studies that focus on CAS as a theory to provide a better explanation on the misalignment issues in mobile application development.